OPSOСLONUS-MYOCLONUS SYNDROME - N. A. Shnayder; E. A. Kantimirova; V. A. Ezhikova (Нервно-мышечные болезни, 2015)
This article provides an overview of the Russian and foreign studies on paraneoplastic opsoсlonus-myoclonus syndrome. Opsoclonus is characterized by involuntary, arrhythmic, chaotic, multi-directional saccades with horizontal, vertical and torsional components, and it is commonly accompanied by cerebellar ataxia and myoclonic jerks in the trunk and limbs. It is a rare neurological disorder of unknown causes which appears to be the result of an autoimmune process involving the nervous system. Paraneoplastic opsoсlonus-myoclonus syndrome is most commonly associated with small-cell lung cancer, breast cancer, ovarian cancer, non-Hodgkin's lymphoma, renal adenocarcinoma. In children, a neuroblastoma is detected in approximately 50% of cases. Many autoantibodies have been detected in patients with paraneoplastic opsoсlonusmyoclonussyndrome: this finding suggests the involvement of a humoral immune mechanism. However, most patients are seronegative for these autoantibodies. Paraneoplastic opsoсlonus-myoclonus syndrome is less responsive to immunotherapy (corticosteroids, intravenous immunoglobulin, adrenocorticotropic hormone, plasma exchange, cyclophosphamide, or rituximab) and improves only with tumor resection. Further studies are needed to further elucidate its immunopathogenesis and pathophysiology in order to develop novel and efficacious therapy.